Opportunities for Listening and for Instruction that Occur During the Learning Process - Sariani Sariani (Politeknik Negeri Padang, 2015)
Teaching a language whether English for Foreign Language (EFL) or English as a Second Language (ESL) always focuses on the four skills: listening, speaking, reading and writing and should have applied into a well-balanced implementation to each. Highlighted by Nunan (1998) that over 50 % of the time spent by the students is for listening in learning a foreign language therefore it plays significant role in language development. The complexity occurs when the teaching-learning process is lack of adequate attention on improving their listening skill rather than testing their comprehension. Therefore by applying principles of ‘Meaning, Interesting, New Language, Understanding, and Stress-free (MINUS)’ might assist the teachers to come up with sufficient techniques to make the students can easily engage and obtain language items. Opportunities are discussed which may lead to a more productive learning time in listening by providing attractive variation of teaching. The desired outcomes for both principles and points of approach can accommodate teachers to develop their students listening skill as has been set in their lesson plan.